Questionnaire-based subjective evaluation and analysis of factors influencing the effectiveness of treatment with the vacuum bell in children with pectus excavatum: a cross-sectional observational study - Zhou, Lihuan; Deng, Fang; Tian, Yunfei; Lin, Jiayi; Yang, Guihong; Li, Yunfei; Latour, Jos M.; Deng, Xicheng (Frontiers in Pediatrics, 2024)
Background: Vacuum bell (VB) is a technique to treat pectus excavatum in children. Its effectiveness and influencing factors, however, remain under investigated. The aim of this study was to examine the therapeutic effect and its influencing factors of VB in children with pectus excavatum. Methods: A cross-sectional observational study was conducted. Parents of children with pectus excavatum who underwent treatment with a VB between January 2018 and December 2019 were recruited. A survey was designed based on previously related studies and delivered to the parents in September-October 2021. The therapeutic effect was analyzed using subjective experiences by parents. Factors related to effectiveness were analyzed through univariate analysis and multivariate logistic regression.Results: Of the 77 surveys distributed, 65 (84%) were returned. The mean duration of VB was 23.20 (SD 9.86) months. Caregivers rated the effect of VB treatment as moderate (41.5%), good (46.2%), excellent (12.3%). There were 39 children (60%) who had at least one pause of using VB for more than two weeks. Univariate analysis showed no significant difference between age, height, weight, duration of VB (months) and the effectiveness of VB therapy as defined by caregivers (p>0.05) and significant difference were observed of the variables 'complication of petechiae' (p=0.034) and 'device returned to manufacturer for repair' (p=0.011). The multivariate logistic regression showed that the occurrence of complication petechiae (p=0.046) was an influential factor for the effectiveness of VB.Conclusions: The evaluations reported by the parents suggested that the VB treatment was effective, although with varying degrees. The complication of petechiae seems an influencing factor to successful VB treatment in children with pectus excavatum. Further studies are needed to assess the long-term outcome and effect of VB and to improve the device and to reduce complications in order to enhance compliance and improve effectiveness.